Evaluation of novel biomarkers in the detection of chemotherapy-mediated cardiac and kidney injury - Jones, Melissa (Trinity College (Dublin, Ireland). Department of Physiology, 2015)
Chemotherapeutic agents are associated with a risk for potential cardiac and kidney injury, however diagnostic techniques currently used to assess cardiac function lack sensitivity, whilst those used to evaluate kidney function display significant variability. Recent studies have suggested that chemotherapy can cause cardiac myocyte injury, myocardial muscle stretch and cardiac remodelling in addition to kidney injury which can increase renal biomarker levels and decrease estimates of glomerular filtration rate (eGFR) and creatinine clearance (CrCl). The purpose of this study was to evaluate the cardiac biomarkers high sensitive cardiac troponin-I (hscTnl), amino-terminal pro-B-type natriuretic peptide (NT-proBNP), galectin-3 and to develop an assay for aldosterone using mass spectrometry. This study also aimed to evaluate the renal biomarkers creatinine, cystatin C and neutrophil gelatinase-associated lipocalin (NGAL) and their diagnostic utility in Cockrofl-Gault (CG), Modified Diet in Renal Disease (MDRD) and Chronic Kidney Disease (CKD-EPl) eGFR formulae in the assessment of kidney function, including in the application of chemotherapeutic drug dosing.
Keywords: Medicine, Ph.D.; Ph.D. Trinity College Dublin.